Results after surgical treatment of liver metastases in patients with high-grade gastroenteropancreatic neuroendocrine carcinomas. Issue 9 (September 2017) - Galleberg, R.B.; Knigge, U.; Tiensuu Janson, E.; Vestermark, L.W.; Haugvik, S.-P.; Ladekarl, M.; Langer, S.W.; Grønbæk, H.; Österlund, P.; Hjortland, G.O.; Assmus, J.; Tang, L.; et al.
Abstract: Background: Gastroenteropancreatic neuroendocrine carcinomas (GEP-NEC) are generally characterized by synchronous metastases, high aggressiveness and a dismal prognosis. Current international guidelines do not recommend surgical treatment of liver metastases, however the existing data are scarce. The aim of this study was to evaluate the results of curatively intended resection/radiofrequency ablation (RFA) of liver metastases in patients with metastatic GEP-NEC. Methods: 32 patients with a diagnosis of high-grade gastroenteropancreatic neuroendocrine neoplasm (Ki-67 > 20%) and with intended curative resection/RFA of liver metastases, were identified among 840 patients from two Nordic GEP-NEC registries. Tumor morphology (well vs poor differentiation) was reassessed. Overall survival (OS) and progression-free survival (PFS) was assessed by Kaplan–Meier analyses for the entire cohort and for subgroups. Results: Median OS after resection/RFA of liver metastases was 35.9 months (95%-CI: 20.6–51.3) with a five-year OS of 43%. The median PFS was 8.4 months (95%-CI: 3.9–13). Four patients (13%) were disease-free after 5 years. Two patients had well-differentiated morphology (NET G3) and 20 patients (63%) had Ki-67 ≥ 55%. A Ki-67 < 55% and receiving adjuvant chemotherapy were statistically significant factors of improved OS after liver resection/RFA. Conclusion: This study shows a long median and long term survival after liver surgery/RFA for these selected metastatic GEP-NEC patients, particularly for the group with a Ki-67 in the relatively lower G3 range. Our findings indicate a possible role for surgical treatment of liver metastases in the management of this patient population.